Synthesis and coordination behaviour of the new (8-quinolyl)cyclopentadienyl ligand - Enders, Markus; Kohl, Gerald; Pritzkow, Hans (Journal of organometallic chemistry, 2001)
8-Bromoquinoline reacts with zincated cyclopentadienyl derivatives of Fe, Mn, and Re in the presence of bis(triphenylphosphine)palladium(0) to yield the corresponding 8-quinolylcyclopentadienyl metal complexes. Tricarbonyl[eta (5)-(8-quinolyl)cyclopentadienyl]manganese(I) (5) and tricarbonyl[eta (5)-(8-quinolyl)cyclopentadienyl]rhenium(I) (6) eliminate CO upon irradiation to form dicarbonyl[eta (5)-(8-quinolyl)cyclopentadienyl]manganese(I) (7) and dicarbonyl[eta (5)-(8-quinolyl)cyclopentadienyl]rhenium(I) (8), respectively. The intensely coloured complexes 7 and 8 show solvatochromism, which has been investigated in more detail. Coordination of the quinolyl moiety in 7 and 8 could be proved by spectroscopy and by crystal structure determination.
Gesehen am 26.02.2018